Limiting global warming to 1.5 °C will lower increases in inequalities of four hazard indicators of climate change. (29th November 2019) - Shiogama, Hideo; Hasegawa, Tomoko; Fujimori, Shinichiro; Murakami, Daisuke; Takahashi, Kiyoshi; Tanaka, Katsumasa; Emori, Seita; Kubota, Izumi; Abe, Manabu; Imada, Yukiko; Watanabe, Masahiro; Mitchell, Daniel; et al.
Abstract: Clarifying characteristics of hazards and risks of climate change at 2 °C and 1.5 °C global warming is important for understanding the implications of the Paris Agreement. We perform and analyze large ensembles of 2 °C and 1.5 °C warming simulations. In the 2 °C runs, we find substantial increases in extreme hot days, heavy rainfalls, high streamflow and labor capacity reduction related to heat stress. For example, about half of the world's population is projected to experience a present day 1-in-10 year hot day event every other year at 2 °C warming. The regions with relatively large increases of these four hazard indicators coincide with countries characterized by small CO2 emissions, low-income and high vulnerability. Limiting global warming to 1.5 °C, compared to 2 °C, is projected to lower increases in the four hazard indicators especially in those regions.